مساهمة التدقيق الداخلي لنظم المعلومات المحاسبية لتقليل من ممارسة المحاسبة الإبداعية - الشيماء شيخة; عائشة مسعودي; منى زاوي (university of eloued جامعة الوادي, 2025)
"تهدف هذه الدراسة إلى إكتشاف مدى مساهمة التدقيق الداخلي نظم المعلومات المحاسبية في التقليل من ممارسة المحاسبة الإبداعية وذلك من خلال طرح الإشكالية المتمثلة في ما مدى مساهمة التدقيق الداخلي لنظم المعلومات المحاسبية لتقليل من ممارسة المحاسبة الإبداعية؟ للإجابة عن هذه الإشكالية المتمثلة يتم إعداد إستبيان يتكون من محورين حيث يتكون من محورين حيث يتكون المحور الأولى من بعدين والمحور الثاني من بعد واحد، حيث تم قياس مستوى ممارسة المحاسبة الإبداعية على مستوى القوائم المالية. وتوصلت هذه الدراسة إلى عدة نتائج أهمها: من خلال نتائج الدراسة الميدانية المتعلقة بمساهمة تدقيق نظم المعلومات المحاسبية في الحد من ممارسة المحاسبة الإبداعية فقد تم توصل لعدة نتائج نذكرها: 1-يساهم التدقيق الداخلي ونظام الرقابة الداخلية في تقليل من ممارسة المحاسبة الابداعية. 2- المحاسبة الإبداعية ممارسة قانونية يمكن ممارستها من خلال استغلال ثغرات القانون في المعايير المحاسبية 3-الهدف من المحاسبة الابداعية هو تعزيز الأداء المالي للمؤسسة، او الاستفادة من المزايا الضريبية وعليه فأن لها المزايا قصيرة الأجل بالنسبة للمؤسسة، ولكن لها سلبيات كثيرة على مستخدمي معلوماتها المالية، بل وحتى للمؤسسة بحد ذاتها في الأمد البعيد. 4-وجود علاقة عكسية بين تدقيق نظم المعلومات المحاسبية وممارسة المحاسبة الإبداعية؛ أي أنه كلما زادت جودة وكفاءة التدقيق؛ قلت فرص ممارسة المحاسبة الإبداعية. 5-يساهم تدقيق نظم المعلومات المحاسبية في تقليل من ممارسة المحاسبة الإبداعية لدى عينة الدراسة. 6-ضعف استقلالية المدقق الداخلي في بعض المؤسسات يحدّ من قدرته على كشف أو الإبلاغ عن ممارسات المحاسبة الإبداعية. "This study aims to explore the extent to which internal auditing of accounting information systems contributes to reducing the practice of creative accounting. This is achieved by addressing the central research question: To what extent does the internal auditing of accounting information systems help reduce the practice of creative accounting? To answer this question، a questionnaire was prepared consisting of two main axes. The first axis includes two dimensions، while the second axis comprises one dimension. The level of creative accounting practices was measured at the level of the financial statements. The study reached several key findings، the most important of which are: 1.Internal auditing and internal control systems contribute to reducing the practice of creative accounting. 2.Creative accounting is a legal practice that can be carried out by exploiting loopholes in accounting standards. 3.The objective of creative accounting is to enhance the financial performance of the organization or to benefit from tax advantages. Therefore، it provides short-term benefits to the organization but has many negative implications for users of its financial information—and even for the organization itself in the long run. 4.There is an inverse relationship between the auditing of accounting information systems and the practice of creative accounting; that is، the higher the quality and efficiency of the audit، the lower the chances of engaging in creative accounting. 5.The auditing of accounting information systems contributes to reducing the practice of creative accounting within the study sample. 6.The lack of independence of internal auditors in some institutions limits their ability to detect or report creative accounting practices."
ماستر
Keywords: نظم المعلومات المحاسبية،; تدقيق داخلي; محاسبة الإبداعية; Accounting Information Systems، Internal Auditing، Creative Accounting.; Accounting Information Systems; Internal Auditing; Creative Accounting.